2004
DOI: 10.1103/physrevstab.7.064801
|View full text |Cite
|
Sign up to set email alerts
|

Induction voltage adders and the induction accelerator family

Abstract: Induction voltage adders (IVA) and induction accelerators of various types are described and their principles and advantages are discussed. The designs and technologies used in the various subsections and components of high-current IVAs are described. Some features of the pulse power that drives IVAs are discussed. Two representative high-current IVAs are briefly described, and characteristics of other IVAs with different features are mentioned. Some other IVA and induction accelerator variants that could be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(41 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…It was suggested that the current shunted to the dustbin wall can be reduced and retrapped to the diode if the diode impedance is reduced [12]. When the diode and cylindrical transmission line impedances mismatch, a retrapping wave [16] returns from the diode, rearranging the sheath current allowing for increased diode current accompanied by voltage decrease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that the current shunted to the dustbin wall can be reduced and retrapped to the diode if the diode impedance is reduced [12]. When the diode and cylindrical transmission line impedances mismatch, a retrapping wave [16] returns from the diode, rearranging the sheath current allowing for increased diode current accompanied by voltage decrease.…”
mentioning
confidence: 99%
“…The sheath is ordinarily shunted to the walls and not incorporated in the diode through direct flow [12] because it was expected that this flow is turbulent and asymmetric. To shunt the sheath away from the diode, the knob in a dustbin is used [2], [13].…”
mentioning
confidence: 99%
“…The Linear Transformer Driver (LTD) is a relatively new pulsed power architecture based on the induction voltage adder (IVA) [6][7][8]. In both systems (IVA or LTD) voltage adder cells are stacked in series and voltage is added along a coaxial vacuum transmission line.…”
Section: Option 2: Linear Transformer Drivermentioning
confidence: 99%
“…downstream imaging can be accommodated), 3) the Area C Spectrometer is not moved/dismantled and thus the system must fit in the existing available footprint, 4) no large external oil storage is provided and thus the systems must be self-contained, 5) there is no existing crane access, 6) electrical and plumbing piping/conduit around the outer walls of the facility can be moved, 7) the costs and schedule associated with facility modifications are not included, 8) and that installation of the radiographic system can occur during pRad "down" time (otherwise schedule will increase)…”
Section: Introductionmentioning
confidence: 99%
“…Older machines at the Atomic Weapons Establishment (AWE) in England are based on marx generator capacitive energy storage and Blumlein pulse compression. Modern radiography accelerators such as RITS [2], Mercury [3], and Hydrus [4,5] use inductive voltage adder (IVA) technology [6]. Inductive voltage adders consist of multiple series IVA cells coupled to a single stalk forming a magnetically insulated transmission line (MITL) which is coupled at the high voltage end to an electron beam diode.…”
Section: Introductionmentioning
confidence: 99%